Impacto Socioeconómico del Microcrédito en la zona urbana de Loja - Guayllas Tamay, Geovanna Elizabeth (2023)
Microcredit is a financial tool aimed at the economic and social improvement of the quality of life of low-income beneficiaries, who seek growth opportunities through entrepreneurship. The general objective of this study was to analyze the socioeconomic impact of microcredit in the urban area of Loja, with this in mind a mixed approach was applied, in which qualitative and quantitative paradigms were covered, the research was descriptive, correlational and explanatory. For the descriptive part, a survey was used in which 384 people who were recipients of microcredit in the period 2017-2019 participated. For the correlational and explanatory part, non-parametric tests such as the Wilcoxon statistic and an Ordered Logit Econometric model were used. The main findings of the research indicate that, 37.8 % of the population under study managed to start an economic activity with the Microcredit, for 55.5 % who already had the microcredit it helped them to enhance their earnings, in the same way when applying the non-parametric Wilcoxon test it is highlighted that the Microcredit did improve social and economic aspects of the beneficiaries. In addition, the variables type of work and self-esteem used in the econometric model are significant and are directly related to the microcredit.